Peran buku cerita terhadap perkembangan kecerdasan linguistik pada anak pra sekolah - Arum, Putri Nirmala (Maliki Interdisciplinary Journal, 2024)
The most important period in a child's growth and development is 0 to 6 years old. Because this period is the golden age for children's brain development. There are various forms of education that can be given to children from an early age onwards. Starting with methods such as singing, playing, telling stories and field trips. Several studies have proven that the storytelling method is an effective method and is most popular with children. The reasons for telling stories can be considered effective for educating children. First, stories are more effective than advice, so stories are generally more embedded in a person's memory. Second, children are taught to learn lessons through (stories). Using the narrative method makes children more comfortable than giving advice. Creating intelligent and successful children requires maximum effort, including the parenting style applied to children. The parenting style that can develop children's potential and creativity is authoritative parenting. Storytelling (storytelling method) can stimulate various children's intelligence from an early age. Storytelling can, among other things, improve children's language skills, creativity and instill morals in young children. However, it should be noted that the cognitive phase of early childhood is still in a certain activity phase, so the form of story used as a storytelling method must be adjusted to the child's abilities.